Agent to the stars - Scalzi, John 1969- (New York Tor, 2005)
The space-faring Yherajk have come to begin humanity's first interstellar friendship. Unfortunately, they are hideous and they smell like rotting fish. They're going to need the best agent in Hollywood to make the friendly, odiferous creatures palatable to humanity.
Keywords: Theatrical agents -- Fiction; Extraterrestrial beings -- Fiction; Human-alien encounters -- Fiction